Preaching Islamic renewal : religious authority and media in contemporary Egypt - Brinton, Jacquelene Gottlieb, 1965- (University of California Press, 2016)
"The book is an in-depth study of Muhammad Mitwall Sha'rawi one of the most important religious figures in late twentieth century Egypt. Sha'rawi was an advisor to the rulers of Egypt as well as being the first Arab television preacher. At the height of his career it was estimated that up to 30,000,000 people tuned in to his show each week. Much of the academic literature that focuses on Islam in modern Egypt repeats the claim that traditionally trained Muslim scholars suffered the loss of religious authority. Sha'rawi however is an example of a well-trained Sunni scholar who became a national media sensation. He used television for the purpose of renewing religion by popularizing long held theological and ethical beliefs."--Provided by publisher